Ownership and Financial Performance in the German Hospital Sector - Boris Augurzky; Dirk Engel; Christoph M. Schmidt; Christoph Schwierz (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
This paper considers the role of ownership form for the financial performance of German acute care hospitals and its development over time. We measure financial performance by a hospital-specific yearly probability of default (PD). Using a panel of hospital data, our models allow for state dependence in the PD as well as unobserved individual heterogeneity. We find that private ownership is more likely to be associated with sound levels in financial performance than public ownership. Moreover, state dependence in the PD is substantial, albeit not ownership-specific.Finally, our evidence suggests that overall efficiency may be enhanced most by closing down some loss-making public hospitals rather than by their restructuring, especially because the German hospital market has substantial excess capacities.
Keywords: I11; I18; 330; Hospitals ownership; financial performance; state dependence; Krankenhausfinanzierung; Eigentümerstruktur; Kreditwürdigkeit; Deutschland